Trace elements in fertilizers used in Peru - Gómez, Víctor (2023)
Fertilizers provide essential nutrients for crops, however, they may also inadvertently provide trace elements that in certain concentrations represent a risk to the soil and the food chain. The objective of this research was to determine the concentrations of Cd, Pb, Cu, and Zn in the most common fertilizers used in Peruvian agriculture. Twenty-one products including inorganic, organic mineral, and organic fertilizers were analyzed by microwave plasma atomic emission spectrometry. The results were compared against international standards. The content of the trace elements was variable and related to the type of fertilizer. Phosphorus fertilizers showed higher concentrations of Cd (3.3-42.3 mgkg-1), most of which exceeded the regulatory limits of several countries. In the case of Pb, none of the fertilizers analyzed exceeded the regulatory limits. Chicken manure showed the highest concentrations of Cu and Zn. The concentration of trace elements such as Cd in fertilizers should be monitored in Peru, since the prolonged and intensive use of phosphorus fertilizers in doses that do not consider technical recommendations, could represent an accumulation of these elements in soils, with the consequent risk to human health and the environment.